UVA precision landing in uncontrolled environment - Lu, Xinpei (Nanyang Technological University, 2021)
The autonomous landing of UAV in an uncontrolled environment has long been the limiting factor for the development of fully autonomous flight, which holds great potential for both commercial and military applications. However, the current approach for autonomous landing requires expensive hardware and extensive tuning to function correctly, which increases the barrier of entry for fully autonomous flight. Therefore, research is needed to develop a cheap and reliable technique for the autonomous landing of UAVs. In this report, an alternative approach to autonomous landing is proposed, which uses off-the-shelf components such as Raspberry Pi, low power Lidar, and fish-eye camera to implement SLAM and fiducial marker detection, which are used for indoor navigation and landing pad detection, respectively. The proposed autonomous landing algorithm uses different control techniques such as PID controllers and optical feedback to ensure the stability of the UAV and its landing accuracy.